590 Influence of Hospital Characteristics on Patient Outcomes Following Cancer Surgery: An International, Mixed Methods Study Across 66 Countries. (12th October 2021) - Knight, S; Weiser, T; Pius, R; Harrison, E; ,
Abstract: Aim: Early death after cancer surgery is higher in low- and middle-income settings, yet the impact of hospital characteristics on early postoperative outcomes following cancer surgery worldwide are unknown. Method: A mixed-methods analysis was performed using data from the GlobalSurg 3 study, a multicentre, international prospective cohort study of patients who underwent surgery for breast, gastric or colorectal cancer. The primary outcomes were 30-day mortality and major complication rates. Hierarchical clustering identified distinct hospital characteristics to create a facility capacity framework. Adjusted outcomes were determined after accounting for patient characteristics and country-income group. Results: Hospital-level data were available for 9685 patients across 238 hospitals. The facility capacity framework consisted of seven distinct hospital resources and processes: presence of CT scan, postoperative recovery area, critical care facilities, opioid analgesia availability, oncologist, pathology and radiotherapy services. While complication rates were similar across hospitals with varying facility capacities, hospitals with five or less capacities (116 hospitals, 2251 patients) had increased mortality (aOR 1.67, 95% CI 1.13-2.48; P = 0.010). After adjustment for case-mix and country income group, patients undergoing surgery for gastric and colorectal cancer in hospitals with reduced capacities had higher mortality (6.2 vs. 4.0%; P < 0.001), predominantly explained by limited capacity to rescue following the development of major complications (61.3 vs. 72.1%; P < 0.001). Conclusions: Hospitals with certain system capacities achieve better outcomes following cancer surgery, independent of country-income group. For cancers amenable to surgical treatment, national cancer care plans should include both surgical capacity building and concurrent hospital facility development to maximise reductions in cancer-associated mortality.